Where is the Depressant? - Ton de Gouw; Ronald Smeink (International Mineral Processing Congress, 2003)
"Reagents are an important cost-factor in the flotation of minerals. The mechanism of collectors and frothers has been studied extensively, but on depressants – probably the biggest cost-factor in the reagent suite – very little is actually known. Theories are frequently faced with the bare facts, pointing in another direction. Fundamental research is complicated by the fact that the amount of possible interactions in the flotation cell is almost unlimited and makes “change-one-parameter-at-a-time” experiments questionable and at least difficult to interpret. Also, the adsorption of depressants on the ore is very strong and desorption merely impossible. Detection methods therefore tend to be indirect and – therefore - non-specific about the location of the depressant on the ore.Depressants are supposed to adsorb selectively on gangue minerals; not on the valuable minerals in the froth. In order to be able to develop better and ‘’smarter’’ depressants, an analytical method is therefore required that will enable to detect which (=qualitatively) depressant, in which concentration (=quantitatively) sits where exactly (= selectively) on the mineral surface. (Answering the question: ‘’ Which minerals is located direct under the depressant?’’)And also: does the depressant compete with other reagents for that location? (like collectors) This analytical method is under development. The actual status of the method is promising and the results will be shown."